Analisis Hubungan Kepuasan dengan Loyalitas Konsumen terhadap Sepeda Motor Yamaha Vixion pada Bengkel Abadi Motor Kebon Jeruk Jakarta Barat - Amalia, Lia (Jurnal Ekonomi : Journal of Economic, 2013)
AbstractWith so many automotive company in Indonesia then the consumer will be more selective in deciding which brand of motorcycle is used as a means of transportation. The emergence of the Chinese motorcycle manufacturers are increasingly tightening competition motorcycle industry in Indonesia. The purpose of this study was to determine whether there is a relationship satisfaction and customer loyalty to Yamaha Vixion. The sampling technique used is nonprobability sampling accidental (accidental sampling). The population in this study is the people who buy and use Vixion Motorcycles Yamaha Motor Kebun in Eternal Repair Orange, West Jakarta. The total population in this study was not counted. Based on the results of the study to 100 respondents and a discussion of the level of consumer satisfaction in using Vixion Yamaha motorcycles can be concluded that consumers in Vixion Yamaha Motor Kebun Timeless Repair Orange, West Jakarta included into the category quite satisfied. Of the five levels of brand loyalty, ie switcher , habitual buyers, satisfied buyer, liking the brand, and committed buyer, based on the calculation of the level of loyalty 100 respondents found that consumers in the Eternal Motorcycle Workshop Kebun Orange, West Jakarta including the level of committed buyer. This means consumers are loyal to Yamaha Vixion and promotes it to others in order to buy a motorcycle Yamaha Vixion brand. Based on the results of the discussion that the customer satisfaction variable (X) has a positive and significant relationship with customer loyalty variable (Y). This is evident from the value ofÂ Spearman Rank correlatioan. Keywords: switcher, habitual buyers, satisfied buyer